Damage caused by larvae of mining fly (Phytomyza agromyzina Meigen, 1830) to dogwoods in urban green spaces - Lazarenko, Marina V.; Buga, Sergey V. (Journal of the Belarusian State University. Ecology, 2021)
According to the results of the investigations, carried out in 2017–2020 in the green spaces of cities in Belarus, the damage caused by larvae of Phytomyza agromyzina Meigen, 1830 to Siberian dogwood (Cornus alba L.) and blood twig dogwood (Cornus sanguinea (L.) Opiz), based on determining the relative area of damaged leaf surface, was assessed. The values of this parameter for individual leaf blades varied in the range from 0.86 to 63.58 %, while the average for the samples did not exceed 24.47 %. The total area of Ph. agromyzina mines on individual Cornus leaf blades ranged from 0.23 to 3.65 cm2. Using the nonparametric Mann–Whitney and Kolmogorov–Smirnov tests, the differences in medians and the integral differences between the samples were estimated. These values were not statistically significant when comparing data for Minsk and Vitebsk, and different years for both C. alba and C. sanguinea. However, in the values of the relative area of the damaged surface between the samples of both Cornus species the differences were statistically significant (p <0.05).